Fatal multidrug-resistant Bordetella bronchiseptica and CAdV-2 coinfection in an 8-month-old boxer puppy, Southern Italy - Gianmarco Ferrara; Francesca Paola Nocera; Michela Arcangela Forgione; Francesco Mira; Filomena Fiorito (Veterinary Research Communications, 2026)

Indoor pollution induced oxinflammatory responses in lung tissues - Mariana Garcés; Alessandra Pecorelli; Andrea Vallese; Natalia Magnani; Francesca Ferrara; Mascia Benedusi; Franco Cervellati; Pablo Evelson; Giuseppe Valacchi (Chemico-Biological Interactions, 2026)

Supramolecular nanosystems for rutin topical application - Maddalena Sguizzato; Francesca Ferrara; Stefano Manfredini; Markus Drechsler; Anna Baldisserotto; Rita Cortesi (Journal of Pharmaceutical Innovation, 2026)
Purpose This study presents the development of supramolecular nanosystems for the topical administration of rutin (RU), focusing on β-cyclodextrin (Cy) complexes and their inclusion in liposomes (CyL) in a 4:1 molar ratio. Methods The supramolecular nanosystems were obtained by the “thin film hydration” method, and characterized in terms of size, morphology, encapsulation efficiency, antioxidant activity and skin safety, by DLS, transmission electron microscopy, UV spectrometry, DPPH radical liberation assay and patch test, respectively. Rutin release kinetics was determined by Franz cell experiments. Results The resulting CyL loaded with RU formed stable, homogeneous vesicular dispersions, maintaining color, size, and polydispersity over 30 days, with rutin content consistently above 90%. Antioxidant activity, assessed by FRAP and DPPH assays, was significantly enhanced when RU was encapsulated in Cy and delivered via liposomes. In vitro diffusion studies using Franz cells revealed that CyL formulations provided a controlled release profile for RU, characterized by an initial increase followed by a plateau, suggesting vesicle-mediated release modulation. To improve topical applicability, CyL and Cy formulations were gelled with carbopol or xanthan gum, resulting in pseudoplastic, non-Newtonian gels. Gels containing CyL exhibited reduced spreadability and increased adhesiveness, supporting effective skin application. Patch tests on healthy volunteers confirmed good skin tolerability of all formulations. Conclusions These findings demonstrate that the combination of cyclodextrin complexation and liposomal encapsulation, followed by gelation, offers a promising dual strategy to enhance the topical delivery and antioxidant efficacy of rutin.

Water use of an irrigated peach orchard treated with different plastic mulching films under Mediterranean climate - Rossana Monica Ferrara; Maria Roberta Bruno; Sergio Ruggieri; Gabriele De Carolis; Pasquale Campi; Onofrio Cappelluti; Alessandro Ciurlia; Pietro Maggi; Anna Francesca Modugno; Alessandro Montaghi; Alessandro Azzolini; Valerio Minorenti; et al. (Irrigation Science, 2025)

Phylosymbiosis and Elevated Cancer Risk in Genetically Depauperate Channel Island Foxes - Alexandra L. DeCandia; Jasmine Lu; Emily E. Hamblen; Lara J. Brenner; Julie L. King; Calypso N. Gagorik; Juliann T. Schamel; Stacy S. Baker; Francesca J. Ferrara; Melissa Booker; Andrew Bridges; Cesar Carrasco; et al. (Molecular Ecology, 2025)
Examination of the host‐associated microbiome in wildlife can provide critical insights into the eco‐evolutionary factors driving species diversification and response to disease. This is particularly relevant for isolated populations lacking genomic variation, a phenomenon that is increasingly common as human activities create habitat ‘islands’ for wildlife. Here, we characterised the gut and otic microbial communities of one such species: Channel Island foxes ( Urocyon littoralis ). The gut microbiome provided evidence of phylosymbiosis by reflecting the host phylogeny, geographic proximity, history of island colonisation and contemporary ecological differences, whereas the otic microbiome primarily reflected geography and disease. Santa Catalina Island foxes are uniquely predisposed to ceruminous gland tumours following infection with Otodectes cynotis ear mites, while San Clemente and San Nicolas Island foxes exhibit ear mite infections without evidence of tumours. Comparative analyses of otic microbiomes revealed that mite‐infected Santa Catalina and San Clemente Island foxes exhibited reduced bacterial diversity, skewed abundance towards the opportunistic pathogen Staphylococcus pseudintermedius and disrupted microbial community networks. However, Santa Catalina Island foxes uniquely harboured Fusobacterium and Prevotella bacteria as potential keystone taxa. These bacteria have previously been associated with colorectal cancer and may predispose Santa Catalina Island foxes to an elevated cancer risk. In contrast, mite‐infected San Nicolas Island foxes maintained high bacterial diversity and robust microbial community networks, suggesting that they harbour more resilient microbiomes. Considered together, our results highlight the diverse eco‐evolutionary factors influencing commensal microbial communities and their hosts and underscore how the microbiome can contribute to disease outcomes.

Effect of Cu- and Fe- Isolated from Environmental Particulate Matter on Mitochondrial Dynamics in Human Colon CaCo-2 Cells - Franco Cervellati; Mascia Benedusi; Alice Casoni; Giulia Trinchera; Andrea Vallese; Francesca Ferrara; Maria Chiara Pietrogrande; Giuseppe Valacchi (Biological Trace Element Research, 2024)

Convenient solutions, inconvenient truths – Why supermarkets will not drive food system transformation - Hanna Helander; Simone Schnepf; Theresa Stetter; Francesca Ferrara; Sina Leipold (Ecological Economics, 2024)

Signature of paraoxonases in the altered redox homeostasis in Alzheimer's disease - Sarah Beggiato; Francesca Ferrara; Arianna Romani; Tommaso Cassano; Alessandro Trentini; Giuseppe Valacchi; Carlo Cervellati; Luca Ferraro (Chemico-Biological Interactions, 2024)

Water use of a super high-density olive orchard submitted to regulated deficit irrigation in Mediterranean environment over three contrasted years - Rossana Monica Ferrara; Maria Roberta Bruno; Pasquale Campi; Salvatore Camposeo; Gabriele De Carolis; Liliana Gaeta; Nicola Martinelli; Marcello Mastrorilli; Anna Francesca Modugno; Teresa Mongelli; Mariagrazia Piarulli; Sergio Ruggieri; et al. (Irrigation Science, 2024)

Inflammasome involvement in CS-induced damage in HaCaT keratinocytes - Roxane Prieux; Francesca Ferrara; Franco Cervellati; Anna Guiotto; Mascia Benedusi; Giuseppe Valacchi (In Vitro Cellular & Developmental Biology - Animal, 2022)
Cigarette smoke (CS) alters cutaneous biological processes such as redox homeostasis and inflammation response that might be involved in promoting skin inflammatory conditions. Exposure to CS has also been linked to a destabilization of the NLRP3 inflammasome in pollution target tissues such as the lung epithelium, resulting in a more vulnerable immunological response to several exogenous and endogenous stimuli related to oxidative stress. Thus, CS has an adverse effect on host defense, increasing the susceptibility to develop lung infections and pathologies. In the skin, another direct target of pollution, inflammasome disorders have been linked to an increasing number of diseases such as melanoma, psoriasis, vitiligo, atopic dermatitis, and acne, all conditions that have been connected directly or indirectly to pollution exposure. The inflammasome machinery is an important innate immune sensor in human keratinocytes. However, the role of CS in the NLRP1 and NLRP3 inflammasome in the cutaneous barrier has still not been investigated. In the present study, we were able to determine in keratinocytes exposed to CS an increased oxidative damage evaluated by 4-HNE protein adduct and carbonyl formation. Of note is that, while CS inhibited NLRP3 activation, it was able to activate NLRP1, leading to an increased secretion of the proinflammatory cytokines IL-1β and IL-18. This study highlights the importance of the inflammasome machinery in CS that more in general, in pollution, affects cutaneous tissues and the important cross-talk between different members of the NLRP inflammasome family.

Actual transpiration and canopy resistance in a Mediterranean vineyard irrigated with saline water - Gianfranco Rana; Rossana M. Ferrara; Francesco Cona; Francesca De Lorenzi (Irrigation Science, 2021)

Evaluation of oxidative damage and Nrf2 activation by combined pollution exposure in lung epithelial cells - Franco Cervellati; Brittany Woodby; Mascia Benedusi; Francesca Ferrara; Anna Guiotto; Giuseppe Valacchi (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Investigating the provenance of Italian archaeological obsidian tools based on their magnetic properties - Enzo Ferrara; Evdokia Tema; Elena Zanella; Cinzia Beatrice; Francesca Miola; Elena Pavesio; Andrea Perino (Archaeological and Anthropological Sciences, 2019)

E-cadherin germline mutation carriers: clinical management and genetic implications - Giovanni Corso; Joana Figueiredo; Roberto Biffi; Chiara Trentin; Bernardo Bonanni; Irene Feroce; Davide Serrano; Enrico Cassano; Bruno Annibale; Soraia Melo; Raquel Seruca; Francesca De Lorenzi; et al. (Cancer and Metastasis Reviews, 2014)

Atmospheric mercury at mediterranean coastal stations - Ingvar Wängberg; John Munthe; David Amouroux; Maria E. Andersson; Vesna Fajon; Romano Ferrara; Katarina Gårdfeldt; Milena Horvat; Yaacov Mamane; Ety Melamed; Mathilde Monperrus; Nives Ogrinc; et al. (Environmental Fluid Mechanics, 2008)